(untitled) (Journal of Economic Research & Business Administration, 2015)
A light industry has an influence on the economic safety of the country while being of great social and economic significance. Though there are necessary conditions for the development of the branch in Kazakhstan, the domestic light industry covers just a small part of the domestic demand. A problem of import dependence is sharp enough. Implementation of governmental programs of branch support produces no significant results. Only a few elements of those programs were realized. Domestic enterprises are not able to compete with foreign ones. A solution of the problem of import dependence is possible only by considerable raise of competitiveness of the domestic light-industry enterprises. In the paper there is analyzed the present state of the light industry in Kazakhstan, studied an import-export ratio for light-industry goods, and there are suggested possible ways to resolve a problem of import substitution.